Exposing the Contested Frames in Strategy Work : Using Visuals to Bridge the Contested Frames - Kohtamäki, Marko; Einola, Suvi; Talaoui, Yassine (Academy of Management, 2018)
There is scant research that pinpoints to the influence framing contests exerts on the sense-making phase of strategy work. Contrary to the foregoing literature on SAP, this paper attempts to draw attention to the conflicts practitioners encounter during strategy work over periods of time, and how, through the use of visuals, practitioners may understand the roots of contestations and possible bridge them. The study utilizes a longitudinal, multi-level data from a case organization, ethnographic action research, and observations from almost 100 strategy workshops, in addition to 26 interviews, and analysis of strategic documents over a 5-year period (2012-2017). Thus, the present study contributes by utilizing antenarratives to understand the collective frames in the city organization, and in particular, by demonstrating how visuals were utilized to create a joint master frame. This paper concentrates on analyzing the cognitive frames constructed and reflected by the antenarratives of municipality strategy and highlights the role of strategy map as a visual tool in bridging framing contestation over a period of 5 years.
Keywords: Strateginen johtaminen